Fish don't play ball - McCann, Emma (Meadowside London, 2004)
"Fish Don't Play Ball" is a humorous children's book that playfully explores the differences between humans and fish. With its whimsical illustrations and rhyming text, this book teaches young readers about the unique characteristics of fish and why they don't participate in human activities like playing ball.